Adaptive Pathways: Possible Next Steps for Payers in Preparation for Their Potential Implementation - Vella Bonanno, Patricia; Ermisch, Michael; Godman, Brian; Martin, Antony P.; Van Den Bergh, Jesper; Bezmelnitsyna, Liudmila; Bucsics, Anna; Arickx, Francis; Bybau, Alexander; Bochenek, Tomasz; van de Casteele, Marc; Diogene, Eduardo; et al. (Frontiers in Pharmacology, 2017)
Medicines receiving a conditional marketing authorisation through Medicines Adaptive Pathways to Patients (MAPPs) will be a challenge for payers. The ‘introduction’ of MAPPs is already seen by the European Medicines Agency (EMA) as a fait accompli, with payers not consulted or involved. However, once medicines are approved through MAPPs, they will be evaluated for funding by payers through different activities. These include Health Technology Assessment (HTA) with often immature clinical data and high uncertainty, financial considerations, and negotiations through different types of agreements, which can require monitoring post launch. Payers have experience with new medicines approved through conditional approval, and the fact that MAPPs present additional challenges is a concern from their perspective. There may be some activities where payers can collaborate. The final decisions on whether to reimburse a new medicine via MAPPs will have more variation than for medicines licensed via conventional processes. This is due not only to increasing uncertainty associated with medicines authorised through MAPPs but also differences in legal frameworks between member states. Moreover, if the financial and side-effect burden from the period of conditional approval until granting full marketing authorisation is shifted to the post-authorisation phase, payers may have to bear such burdens. Collection of robust data during routine clinical use is challenging along with high prices for new medicines during data collection. This paper presents the concept of MAPPs and possible challenges.Concerns and potential ways forward are discussed and a number of recommendations are presented from the perspective of payers.